Transcatheter Mitral Valve-in-Valve Implantation With a New Transcatheter Heart Valve for Bioprosthetic Degeneration - Lu, Yuntao; Yang, Ye; Wang, Wenshuo; Chen, Jinmiao; Yin, Minyan; Huang, Liqi; Dong, Lili; Wang, Chunsheng; Wei, Lai (Frontiers in Cardiovascular Medicine, 2022)
Background Transcatheter mitral valve-in-valve (TMVIV) procedure with aortic transcatheter heart valves has recently become a less invasive alternative for patients with mitral bioprosthetic dysfunction. This study reports the initial experience of TMVIV implantation using the J-Valve System (JieCheng Medical Technology Corporation Ltd., Suzhou, China). Methods A retrospective observational multicenter study was conducted to evaluate the short-term outcomes of TMVIV. In total, 26 consecutive patients with symptomatic bioprosthetic failure at eight hospitals underwent TMVIV using the J-Valve System between May 2019 and June 2021. Procedural results and clinical outcomes were analyzed using the Mitral Valve Academic Research Consortium criteria. Results The mean age was 75.3 ± 7.1 years and 69.2% of patients were female. The mean Society of Thoracic Surgeons Predicted Risk of Mortality score was 12.3 ± 8.3%. The technical success rate was 96.2%. Nine of the 26 patients (34.6%) were implanted with a J-Valve of a size equal to the internal diameters of the deteriorated prostheses. At the 30-day and 1-year follow-ups, all-cause mortality was 3.8 and 16.0% and the stroke rates were 0 and 12.0%, respectively. Device-related mortality was 0% and the mean mitral valve gradient was 6.4 ± 2.7 mm Hg. No patient experienced device embolization, left ventricular outflow tract obstruction, or mitral valve reintervention. Postprocedural mitral regurgitation was none or trace in all the patients. All the patients were in the New York Heart Association (NYHA) class ≤ II at the last follow-up. Conclusion: Transcatheter implantation of the J-Valve System in high-risk patients with mitral bioprosthetic dysfunction was found to be a reasonable alternative and associated with good short-term outcomes.